Indução à triploidia no tambaqui Colossoma macropomum, pacu Piaractus mesopotamicus e o respectivo híbrido tambacu - Sato, Lucas Seiti [UNESP] (2015)
In the present study, we evaluated the triploidy induction efficiency in two species (pacu Piaractus mesopotamicus and tambaqui Colossoma macropomum) and their respective interspecific hybrid tambacu (♀ tambaqui x ♂ pacu). The main objective was to evaluate the heat and cold shock temperatures and the form of identification of the fish ploidy. Furthermore, a protocol has been standardized to obtain mitotic chromosomes from larvae (larvae cytogenetics). In the evaluations of quantity and quality of metaphases, we observed better results for larvae cytogenetics using the concentration of 0.007% (4 hours). Initially, in the pilot experiments, we analyzed heat and cold shock treatments in pacu and tambaqui, which showed better results from hatching rate and triploid index in heat temperatures. Thus, only heat shocks were evaluated in the final experiments. In pacu, 11.8% of triploid juveniles were detected by cytogenetic method in the shock induction at 43 °C (2 min), 2 min after fertilization. For tambaqui, 80% of triploid were detected in larvae cytogenetic analysis for the shock at the 43 °C (2 min), 2 min after fertilization; however, when analyzed in the juvenile stage, we observed 29.4% of triploids. For the hybrid tambacu, we detected 33.3% of triploids in the larval stage at the shock at 43 °C (2 min), 2 min after fertilization; and 8.7% in the juvenile stage. However, in the shock at 41 °C (2 min), 1 min after fertilization, we detected 57.8% of triploid in the juvenile stage. When the ploidy level was analyzed by Nucleolar Organizer Regions analysis (NOR) on metaphase chromosomes, intra-individual variation was found (multiple NOR) for pacu, tambaqui and tambacu, as well as the analysis of interphase nuclei tambaqui, preventing this technique for verification of ploidy. In conclusion, although this study did not reach 100% triploidy, this work enables the triploid production for future studies and identifies them in the ...